Optimising convolutional neural networks for large-scale neuroimaging studies - Dinsdale, NK (2021)
Ageing has a pronounced effect on the human brain, leading to cognitive decline and an increased risk of neurodegenerative diseases. Thus, the ageing population presents a significant challenge for healthcare. The use of MRI and the availability of computational methods for analysing the MRI data is increasingly contributing to the understanding of healthy and diseased structural brain maturation and ageing. Increasingly, large cross sectional and longitudinal neuroimaging studies are becoming available, presenting opportunities for the application of deep learning to neuroimage analysis. There are however, many domain specific problems for applying deep learning to neuroimaging problems, which currently limit their wider applicability.